Case Report: A Case of Hailey–Hailey Disease Mimicking Condyloma Acuminatum and a Novel Splice-Site Mutation of ATP2C1 Gene - Dai, Yuwei; Yu, Lingling; Wang, Yu; Gao, Min; Wang, Peiguang (Frontiers in Genetics, 2021)
Hailey-Hailey disease (HHD) is a rare autosomal dominant blistering disorder characterized by flaccid blisters and erosions at intertriginous sites. We described a 24-year-old male who presented with multiple bright red verrucous papules in his mons pubis, bilateral groins, scrotum, perineum, and crissum, clinically resembling condyloma acuminatum. The histopathology showed extensive acantholysis with the characteristic appearance of a dilapidated brick wall. The mutation analysis revealed a novel splice-site mutation in ATP2C1 gene. The patient was definitely diagnosed as HHD. The antibacterial treatments resulted in significant improvement of cutaneous lesions. Our findings help to broaden the understanding of clinical manifestations of HHD and improve clinical diagnosis and treatment of this disease.